Evaluation of Mutual Funds Performance in Bangladesh: Investors and Market Perspective (Global Journal of Management and Business Research, 2017)
Net assets value is the widely used techniques to know the fund's overall performance. NAV calculation of mutual funds in Bangladesh is guided by Bangladesh securities exchange commission (BSEC). Sharpe ratio, Treynor ratio and Jensen's Alpha are the three popular indicators that are used by investor and researcher to know the performance of mutual fund. In this paper an attempt is made to evaluate the performance of 31 growth oriented mutual funds on the basis of weekly NAV and Weekly close price compared to benchmark returns. For this purpose, risk adjusted performance measures suggested by Jenson, Treynor and Sharpe are employed widely known as Treynor ratio, Sharpe ratio, and Jensen's alpha. This study found that over the research period selected mutual funds shows large negative return than and downward trend in comparison to market return.
Keywords: mutual funds; performance evaluation and bangladesh